Fortalecimiento del turismo de moliendas en el barrio Pitá alto, del cantón Yantzaza, provincia de Zamora Chinchipe - Guarnizo Sánchez, Vanessa Fernanda (2022)
The present research work Touristie Strengthening of Grindings from the Pita Alto Neighborhood in Yantzaza Town, Zamora Chinchipe Province" has the general objective of strengthening the tourism on grindings within the neighborhood since it has the potential to carry out, but for this achievement; it is necessary to se strategies who allow this zone to be developed touristically in this way, three specific objectives were saled: first. To design a touristic diagnostic of the current situation of grindings in Pita Alto Neighborhood, Yantzaza Town, Zamora Chinchipe Province, which allow to know what the reality of the study zone is and its influence zone by the application of the touristic matrix provided by Carla Ricuarta who allowed to know some key points such as the touristic infrastructure of the neighborhood, demonstrating the inexistence of it in the study zone, becoming in a reason for the tourists not to develop their visit to the place appropriately. Thanks to the MINTUR records, It was able to know and develop the hierarchy of the existent attractions, especially from the grindings located in the Pita Allo Neighborhood. Together with this, a market study was applied through the surveys, a FODA analysis and a crossed FODA for getting results that allowed determining the existent problematic in the study zone in such a way that the second objective can be developed: To set the proposal for the touristic strengthening of the grindings in the Pitá Alto Neighborhood, Yantzaza town, Zamora Chinchipe Province, in which it was possible to determine the components and proposals for this researching project. developing the technical, administrative and legal viability of Il basing on the food and drinks regulation purposed by the MINTUR. Likewise, a touristic signage manual was needed for the respective signaling with pictograms of touristic attractions and services which are predicted to be collocated. With this, the last objective is given: To evaluate the economical financial profitability of the stated proposal for the Pitá Alto neighborhood, Yantzaza town, Zamora Chinchipe Province, which through the camp observation and thanks to the proposal of services and products for implementing such as: guiding, trying of products, cadies combos, guarapo, among others; it was possible to know that the project had an actual net value of $257 307 dollars and an internal rate of efficiency of 50,57% which means it is totally profitable The results allowed giving a way to the project to have a suitable direction towards the touristic development of the locality starting from the multiple initial problems like not having the 5 needed touristic infrastructure, they represent being an enough reason to avoid a touristic development of this zone. Finally, it was taken into account some conclusions and recommendations, the last ones especially directed to the Yantzaza GADM. who are the ones in charge on developing the different projects of the town. In the same way, it was especially concluded that this work will be useful not only to encourage the touristic activity, but also it will help to the creation of new sources of employment and with it the increase of economic benefits for its habitants as well as the recognition of Yantzaza Town regarding to what the touristic ambit concerns.